Mechanism of gas cell stability in bread making - Sroan, Baninder Singh (Kansas State University, 2007)
Expansion of dough and hence breadmaking performance is postulated to depend on a dual mechanism for stabilization of inflating gas bubbles. Two flours were used in this study, one from the wheat variety Jagger (Jagger) and the other from a composite of soft wheat varieties (soft). The primary stabilizing mechanism is due to the gluten-starch matrix surrounding the bubble. The secondary mechanism operates when gas bubbles come into close contact during later proofing and early baking. When discontinuities occur in the gluten-starch matrix surrounding gas bubbles, thin liquid lamellae stabilized by adsorbed surface active compounds, provide a secondary stabilization. A key parameter in the primary stabilizing dough film is thought to be the property of strain hardening. Jagger flour gave higher test-bake loaf volume than soft wheat flour and higher strain hardening index for dough. Rheological properties of doughs were varied by addition of protein fractions prepared by pH fractionation. Fractions were characterized by SE-HPLC and MALLS. The molecular weight distribution (MWD) of fractions progressively shifted to higher values as the pH of fractionations decreased. Mixograph peak development time paralleled the MWD. However, the strain hardening index and the test-bake loaf volume increased with increasing MWD up to a point (optimum), after which they declined. At a given strain rate the behavior at the optimum appeared to result from slippage of the maximum number of statistical segments between entanglements, without disrupting the entangled network of polymeric proteins. Shift of MWD to MW higher than the optimum results in a stronger network with reduced slippage through entanglement nodes, whereas a shift to lower MWs will decrease the strength of the network due to less number of entanglements per chain. In order to study the secondary stabilizing mechanism, different lipid fractions were added incrementally to the defatted flours. No effects were observed on the rheological properties of the dough. However, large effects on the loaf volume were measured. The additives used were the total flour lipid and its polar and non polar fractions and the fatty acids palmitic, linoleic and myristic. Polar lipids and palmitic acid had positive or little effect on loaf volume respectively. Non polar lipid, linoleic and myristic acids had negative effects on loaf volume. 1 The different effects of the lipid fractions are thought to be related to the type of monolayer that is formed. Polar lipid and palmitic acid form condensed monolayers at the air/water interface whereas non polar lipid, linoleic and myristic acids form expanded monolayers.
Keywords: Bread making; Gas cell stability; Liquid lamellae; Gluten-starch matrix; Monolayer formation at gas-liquid interface; Rheology of gluten film; Agriculture, Food Science and Technology (0359); Agriculture, General (0473); Engineering, Chemical (0542)